Water stress in beans by decrease in osmotic potential - Garcia, Soraya Helena; Rozzetto, Diane Simon; Coimbra, Jefferson Luís Meirelles; Guidolin, Altamir Frederico (Revista de Ciências Agroveterinárias, 2012)
Water stress is one of the more external agents that damage the development of the bean that has a low capacity to recover after a period of drought. This experiment aimed to evaluate the effect of osmotic solutions of manitol for simulation of water stress during the germination of beans belonging to the Active Germplasm Bank of Imegem, enabling the identification of genotypes tolerant to drought, so they can be included programs in plant breeding. The experiment was conducted at the Science Center Agroveterinary in Lages, SC using four common bean genotypes in a completely randomized design with four replicates for assessment of germination, hypocotyls and radicle of seedlings. Among the genotypes used BAF9 had the better performance for both traits and found to be more adapted to water stress, a characteristic important for breeding programs.